A transition from conventional irrigation to fertigation with reclaimed wastewater: Prospects and challenges. (September 2020) - Chojnacka, K.; Witek-Krowiak, A.; Moustakas, K.; Skrzypczak, D.; Mikula, K.; Loizidou, M.
Abstract: The aim of this review was to discuss the transition from traditional irrigation to fertigation using reclaimed wastewater in countries with moderate climate. In most European countries there are no regulations on waste water reuse and on the other hand there are countries where regulations are very strict. An important aspect is to standardize the restrictions, which would minimize uncontrolled use of wastewater for fertigation. Wastewater is a source of plant nutrients and organic matter, but can be contaminated with chemicals and pathogens, which in turn can lead to secondary environmental pollution. The reuse of recovered wastewater may require modification of the wastewater treatment process line or construction of stabilization tanks at farms. In both cases, it is necessary to set up initial installations in real systems in order to develop principles for irrigation with reclaimed wastewater for soil and temperate climate conditions. The additional treatment steps required are also associated with large investments, but could reduce fertilization costs and, more importantly, improve the environmental situation. The current scale of fertilizer application does not allow conventional fertilization to fulfill global demand. The introduction of such a solution is a step towards the practical application of circular economy and sustainable crop production. The paper discusses a challenges related with implementation of transition from conventional irrigation to fertigation with reclaimed wastewater in moderate climate countries. A special focus to providing fertilizer nutrients in terms of required doses was undertaken. Graphical abstract: Image 1 Highlights: Reclaimed wastewater has the potential for recovering water and nutrients. New EU regulations for the fertigation of treated wastewater should be introduced. Permanent monitoring of reclaimed water and soil is necessary during fertigation. Practical benefits and challenges for wastewater fertigation are indicated.